A new pathway: how can funders support meaningful monitoring, evaluati on, and learning practice in the field? - Acevedo, Andrea; Colnar, Megan (2023)
How can donors and grantees work together to create effective monitori ng, evaluation, and learning (MEL) practices that drive field-wide tra nsformation?